2018
DOI: 10.31955/jimea.vol1.iss1.pp1-9
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Return on Assets, Debt to Assets Ratio, Dan Opini Audit Terhadap Audit Delay

Abstract: This research is performed in order to test the influence of  the variable ROA, DAR and audit opinion toward Audit Delay to the company of manufactur sector basic industrial and chemical in BEI for periode 2013-2014 Analysis technique used is multi regression and hypothesis test use t-statistic to test coefficient of regression partial. The analyse result indicate that data ROA and Audit Opinion in partial significant toward Audit Delay. DAR in partial not significant toward Audit Delay. Anova test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…The rejection of this second hypothesis indicates that DAR does not have a significant effect on the length of time to complete the audit report. The effect of DAR on audit delay in this study is in accordance with the results conducted by (Sumartini and Widhiyani 2014), (Subhan 2015), (Lestari 2018), (Suarsa 2018) and (Ramadhany, Suzan, and Dillak 2018). H3.…”
Section: Normality Testsupporting
confidence: 92%
See 1 more Smart Citation
“…The rejection of this second hypothesis indicates that DAR does not have a significant effect on the length of time to complete the audit report. The effect of DAR on audit delay in this study is in accordance with the results conducted by (Sumartini and Widhiyani 2014), (Subhan 2015), (Lestari 2018), (Suarsa 2018) and (Ramadhany, Suzan, and Dillak 2018). H3.…”
Section: Normality Testsupporting
confidence: 92%
“…The effect of debt ratio on audit delay has been studied by (Lianto 2010), (Kartika 2011) and (Kharissa 2014) who concluded that solvency has an effect on audit delay. However, based on the results of research (Subhan 2015), (Lestari 2018) and (Suarsa 2018) found opposite results where solvency has no effect on audit delay.…”
Section: Literature Reviewmentioning
confidence: 95%
“…A positive and significant relationship was found between the Debt to Assets Ratio (DAR) and Net Profit Margin (NPM) as a result of a study conducted by Shabrina (2020). Furthermore, the results of the DAR study have an effect but not significant on Audit Delay according to Suarsa & Nawawi (2018). The results of studies that show DAR has a significant positive effect on earnings quality according to Kurniawan & Suryaningsih (2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…(kharissa & Saifi, 2018) Menurut penelitian (Suarsa & Nawawi, 2018) Roa secara parsial menunjukkan pengaruh terhadap audit delay , sama hal nya dengan penelitian (Anggraeni, 2012) yang menunjukkan hal yang sama.…”
Section: Pengaruh Roa Terhadap Audit Delayunclassified
“…Terdapat hubungan signifikan antara ROA dan audit delay dengan t-hitung 5,5331 dengan nilai signifikansi 0,000 dibawah standar 5%(0,005). Ini berarti H2 diterima , hal ini didukung juga oleh penelitian (Suarsa & Nawawi, 2018).…”
Section: Pengaruh Roa Terhadap Audit Delayunclassified